Increasing Work Productivity through Job Design and Job Satisfaction among Service Workers: A Case Study at an XYZ Hotel in Bandung City - Anggapradja, Indra Taruna (CENTRAL ASIA AND THE CAUCASUS, 2022)
Hotel XYZ is a hotel that elevates the rustic industrial concept in the city of Bandung. As a hotel that has a good reputation, this hotel has a unique concept, namely applying the concept of 24-hour check-in so that it is very helpful for visitors not to rush with check-in times like in other hotels. The condition of the covid19 pandemic invites various uncertainties for this hotel, income and occupancy rates have drastically decreased, making the policy of many employee layoffs and causing discomfort for employees. This study was conducted to determine the effect of job design and job satisfaction on work productivity which continues to decline. This study uses a population of 77 employees of the XYZ hotel. This research uses verification and descriptive research methods. Based on the hypothesis testing that has been done, it is found that the two variables, both job design and job satisfaction, have a significant effect on work productivity. The author gives suggestions for this research, namely the company must carry out job redesign, fair shift distribution, and improvement of the compensation system.